(Mis)measuring competitiveness: the quantification of a malleable concept in the European Semester - Claudius Gräbner-Radkowitsch; Theresa Hager (ZOE. Institut für zukunftsfähige Ökonomien, 2021)
This paper studies the conceptualization and quantification of 'competitiveness' within the main policy coordination framework of the EU, the European Semester. This topic warrants attention since 'competitiveness' is not only of central importance in the European policy discourse, but also a theoretically ambiguous and malleable concept with conflicting accentuations, all of which are subject of considerable academic and political debate. By investigating the translation of competition as a contested theoretical concept into concrete indicators within a legally binding document, the paper produces three main insights that deserve further attention, both scientifically and politically. First, the indicators of the semester mainly measure cost rather than technological competitiveness, indicating a constriction of the concept at the operational level. Second, while EU policy documents regularly stress the competitiveness of the European Union as a whole, the indicators in the semester measure individual country competitiveness. Finally, the indicators in the Semester measure how the competitiveness of single Member States changes over time, not how they perform relative to others. This shallows the heterogeneity of countries, which is problematic given recent findings according to which absolute differentials of competitiveness across Member States is one important driver of accelerating polarization patterns in the Union.
Keywords: 330; European Union; competition; performativity; European semester; political economy